2014
DOI: 10.1007/s10519-014-9691-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Ethanol’s Anxiolytic Effect and Chronic Ethanol Withdrawal Severity in Mice with a Null Mutation of the 5α-Reductase Type 1 Gene

Abstract: Manipulation of endogenous levels of the GABAergic neurosteroid allopregnanolone alters sensitivity to some effects of ethanol. Chronic ethanol withdrawal decreases activity and expression of 5α-reductase-1, an important enzyme in allopregnanolone biosynthesis encoded by the 5α-reductase-1 gene (Srd5a1). The present studies examined the impact of Srd5a1 deletion in male and female mice on several acute effects of ethanol and on chronic ethanol withdrawal severity. Genotype and sex did not differentially alter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 65 publications
0
20
1
Order By: Relevance
“…LORR duration, taken as an index of sensitivity to the acute intoxicating effects of an ethanol challenge, did not differ between males and females, either in CIE-exposed mice or in air-exposed controls. The absence of an overall sex difference on this measure contrasts with the recent finding of shorter LORR duration in females to a similar ethanol challenge dose as used here (Tanchuck-Nipper et al, 2015). Given that genetic background strongly influences mouse LORR (Boyce-Rustay et al, 2008; Crabbe, 2012; Crabbe, Metten, Cameron, & Wahlsten, 2005) and the mice tested by Tanchuck-Nipper and colleagues were on a C57BL/6J × 129/SvJ background (as opposed to the pure C57BL/6J background used here), a plausible explanation for this discrepancy is that sex differences in the LORR are background-dependent.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…LORR duration, taken as an index of sensitivity to the acute intoxicating effects of an ethanol challenge, did not differ between males and females, either in CIE-exposed mice or in air-exposed controls. The absence of an overall sex difference on this measure contrasts with the recent finding of shorter LORR duration in females to a similar ethanol challenge dose as used here (Tanchuck-Nipper et al, 2015). Given that genetic background strongly influences mouse LORR (Boyce-Rustay et al, 2008; Crabbe, 2012; Crabbe, Metten, Cameron, & Wahlsten, 2005) and the mice tested by Tanchuck-Nipper and colleagues were on a C57BL/6J × 129/SvJ background (as opposed to the pure C57BL/6J background used here), a plausible explanation for this discrepancy is that sex differences in the LORR are background-dependent.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding resembles an earlier report that females from high- and low-ethanol-preferring selected lines did not increase drinking after CIE, though males from these lines (unlike C57BL/6J males) also failed to do so (Lopez et al, 2011). One interpretation of these data is that female mice are protected from chronic ethanol effects on drinking, as they are from its effects on anxiety-like behavior and withdrawal hyperexcitability (Alele & Devaud, 2007; Devaud & Chadda, 2001; Janis et al, 1998; Lopez et al, 2011; Overstreet et al, 2004; Reilly et al, 2009; Strong et al, 2009; Tanchuck-Nipper et al, 2015; Varlinskaya & Spear, 2004; Veatch et al, 2007). Indeed, it is possible that these various behavioral effects are related, such that elevated withdrawal severity and anxiety-like behavior is a driver of elevated drinking in males that is absent in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol withdrawal has also been shown to be reduced in female versus male mice, and this may be related to the increased activity of progesterone and endogenous neurosteroids (Tanchuck-Nipper et al, 2015). Increased levels of progesterone and allopregnanolone are associated with less intense alcohol withdrawal symptoms (Martin-Garcia and Pallares, 2005).…”
Section: Sex Differences In Drug Abusementioning
confidence: 99%
“…Recently, we examined the influence of Srd5a1 deletion in intact male and female mice on several acute effects of ethanol and found that genotype and sex did not differentially alter ethanol-induced hypothermia, ataxia, hypnosis, or metabolism (see companion article; Tanchuck-Nipper et al 2014). However, deletion of the Srd5a1 gene significantly decreased ethanol's effect on total entries in the elevated plus maze, which is an index of activity, versus WT mice and significantly decreased ethanol's anxiolytic effect, measured by percent open arm entries and time, in female KO versus WT mice.…”
Section: Introductionmentioning
confidence: 99%